Technology: nursing the system. Wireless communications: a new frontier in technology. - Simpson RL (Nursing Management)
Within the last 5 to 10 years, health care has seen a plethora of 'break through' technologies -- client/server computing, multitasking, multiuser operating systems, E-mail, CD-ROM data storage, the Internet, etc. Now, a newer technology is coming of age. This point-of-care technology uses radio-based systems to transmit signals through the air without physical connections.